Roteiro para elaboração do plano museológico: o Museu da Farmácia como exemplo de aplicação - Ingrid da Silva Borges (2022)
The development of this work took place through the search for a solution to a need perceived during the experience that has been developed at the Pharmacy Museum (MF) of the Federal University of Ouro (UFOP). Among the many needs of a museum institution is that of building a museum plan, a fundamental tool for the functioning and development of institutions. Despite the importance of the plan, most institutions still do not have this tool and, when we analyze university museums, this number may be even higher, due to their specificities. Seeking to meet this need, we propose in this work a tool that can assist in the construction of the plan by university museums.